The Role of Legal Aid at the Muhammadiyah University of North Sumatra in Divorce Prevention - Erwin Asmadi; Rachmad Abduh (International Journal Reglement & Society (IJRS), 2021)
Indonesia is a rule of law, which is contained in the 1945 Constitution (Yahman & Nurtin Tarigan, 2019: 16). In a rule of law, the state guarantees equality before the law and recognizes and protects human rights, so that all people have the right to be treated equally before the law (equality before the law). Equality before the law must also be accompanied by equal treatment, one form of equality of treatment is the provision of legal aid to the poor and illiterate to achieve equitable access to justice. The form of legal assistance is the existence of a defense or assistance from an advocate (access to legal counsel). Legal aid standards in litigation are implemented in case handling: (a) Criminal; (b) Civil Code; and (c) State Administration. Types of non-litigation Legal Aid activities carried out by Legal Aid Providers include: (a) Legal Counseling; (b) Legal Consultation; (c) Investigation of cases, both electronically and non-electronically; (d) Legal Research; (e) Mediation; (f) Negotiation; (g) Community Empowerment; (h) Outside court assistance; and (i) Drafting legal documents.